The role of sincerity (ikhlas) in coping with depressive symptoms among student in schools: A narrative literature review - Vina Fadhilatu Faizah; Rosyadi, Royan (Creative Smart Visionary, 2025)
Depression among school students is a mental health problem that affects the learning process, academic motivation, and psychological development of students. In the context of educational psychology, adaptive coping strategies are needed that are in harmony with the characteristics of student development as well as cultural and religious values. This study aims to examine the role of sincerity as a form of spiritual coping in dealing with symptoms of depression among students in the school environment and to explore its implications for the practice of educational psychology and school guidance and counseling services. The study uses a narrative literature review approach from scientific articles published between 2020 and 2025 and obtained from accredited academic databases. A total of 12 articles discussing student mental health, academic stress, religious coping and educational psychology were analyzed thematically and narratively. The results of the literature review show a consistent pattern of findings that suggest that sincerity, as well as related concepts such as acceptance and tawakal (trust in God), are often associated with students' ability to cope with academic stress, manage negative emotions, and maintain psychological well-being. The literature reviewed also shows that the value of sincerity helps students interpret academic stress more adaptively and supports emotional stability. Conceptually, sincerity is in line with the principle of acceptance in modern psychology and can be positioned as a potential supporting factor in the psychological development of students in school. These findings emphasize the importance of integrating the value of sincerity into religious education, character education, and Islamic educational psychology-based school guidance and counseling services to support students' psychological well-being holistically and contextually.